Pengaruh Corporate Turnaround Terhadap Financial Distress Dengan Variabel Kontrol Free Assets Dan Firm Size - Ronowati Tjandra; Ratna Puji Astuti; Ivana Octaria Sopacua; Kinasih Kinasih (ITB AAS INDONESIA, 2022)
This article describes the results of empirical research that investigates the effect of downsizing, expenses retrenchment, and assets retrenchment on the success of corporate turnaround using firm size and free assets indicators as control variables in trading sector companies for the 2015-2019 period, which experienced financial distress. The sample used in this study was selected using a purposive method and resulted in a sample of 117 trading company sectors with a total observation of 585 company-years. The measurement of the category of companies in financial distress and the determination of the success of the turnaround is calculated using the Zmijewski method. This study obtained evidence that downsizing, expenses retrenchment, and assets retrenchment had no significant positive effect on the success of corporate turnaround. Free assets as control variables need to be maintained because they have a significant positive effect on downsizing, expenses retrenchment, and assets retrenchment on the success of corporate turnaround.